Sustaining Total Quality Management and ISO 9001 in Valenzuela, Philippines - Patrick De Leon (The Indonesian Institute of Science and Technology Research, 2026)
Administrative Order No. 161, Executive Order No. 605, and the current government policy on the grant of the performance-based bonus (PBB) have made the ISO 9001 Total Quality Management (TQM) model a part of the productivity and performance measurement and quality improvement programs of the Philippine Government. This study identified the factors that affect the sustainability of TQM and ISO 9001 adoption at the City Government of Valenzuela. The needed data for the study were obtained through face-to-face interviews with the aid of a questionnaire from 2017 to 2019. The study found the following as the sustainability factors for TQM and ISO 9001 adoption in Valenzuela: (1) six key elements for TQM implementation by Besterfield et al. (2003), namely, senior management commitment and/or the presence of a driver, quality council, middle managers or supervisors, communication, training, and customer, employee, and supplier surveys; (2) consideration of Filipino cultural values by Andres (1996); and (3) the frequency and nature of leadership change by De Leon (2017). The study recommends: (1) recognizing that TQM and ISO 9001 adoption involves a political process; (2) seeking a broad-based support to ensure that no single person owns the adoption process; (3) eliminating the need to train new implementors through succession planning: (4) avoiding conflicts by leveraging Filipino cultural values; (5) establishing a government agency to provide ISO 9001 certificates; (6) giving recognition, such as the Philippine Quality Award, to encourage TQM adoption; and (7) conducting studies that focus on leadership change, TQM and ISO 9001 internalization, minimizing employee resistance, and the economic benefits of TQM and ISO 9001 adoption.